2012
DOI: 10.1016/j.otsr.2012.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of proximal humerus fractures managed in a trauma center

Abstract: Proximal humerus fractures (PHF) are osteoporotic fractures that affect women over 70 years of age. Like fractures of the femoral neck they have become a public health concern. As the population ages there is an increase in the number of people in poor general condition with an increased risk of falls on fragile bones. The incidence of these fractures has increased by 15% per year. All patients managed for PHF in our center in the past year were included in this prospective study (prospective cohort study; lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
108
2
13

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 189 publications
(145 citation statements)
references
References 14 publications
7
108
2
13
Order By: Relevance
“…Roux et al in 2012 reported that three percent of neck of humerus fracture are associated with epilepsy (Roux et al 2012). It is also known that posterior shoulder dislocation is more common following an epileptic seizure (Court-Brown et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Roux et al in 2012 reported that three percent of neck of humerus fracture are associated with epilepsy (Roux et al 2012). It is also known that posterior shoulder dislocation is more common following an epileptic seizure (Court-Brown et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…It accounts to about 4-5% of all fracture [3,4] . Studies show that more that about 70% of the patients who present with proximal humerus fractures are above the age of 50 years [5,6] .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies indicate that 80% of proximal humeral fractures are recognized as type 1 without displacement, according to the Neer classification [5], and can be successfully managed by non-surgical methods [6,7]. However, it should be noted that the later studies conducted by Court-Brown and Roux described a significantly lower percentage of minimally displaced fractures, ranging from 42% to 49% [8,9]. Literature on the subject of displaced or complex fractures describes no clear indications or qualification criteria for any particular invasive treatment, as a result of uncertain influence on prognosis [8,10].…”
Section: Introductionmentioning
confidence: 99%